Performing a forward dive with 5.5 somersaults in platform diving: simulation of different technique variations - Heinen, T.; Supej, M.; Cuk, I. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Performing dives with multiple somersaults is an inherent component of competitive diving. In individual international competitions, dives are performed from a 1- or 3-m springboard as well as from a 10-m platform, and divers use different technique variations in accelerating and decelerating rotation about the somersault axis. Therefore, the first aim of this study was to evaluate the effect of different technique variations in accelerating and decelerating rotation about the somersault axis in a 109C dive (4.5 forward somersault in a tucked posture) by means of a multi-body computer simulation model based on the real performance of an expert diver. The second aim was to evaluate the feasibility of adding an additional somersault rotation to the 109C dive. The results revealed that different technique variations accounted for different amounts of gain and loss in somersault rotation, whereas no isolated technique variation accounted for an additional somersault rotation. Applying an optimized technique variation together with an increase in angular and linear momentum allowed the simulation model to perform a forward dive with 5.5 somersaults under achievable biomechanical constraints (1011C dive). It is concluded that the 1011C would be a feasible skill for a diver whose sensory-motor system is adequately adapted to withstand angular velocities of approximately 1200°/s and who is able to perform a double tucked somersault in a split-tuck posture above the platform level. Implications for changes in training practices and platform equipment are discussed.